2019
DOI: 10.1111/eea.12748
|View full text |Cite
|
Sign up to set email alerts
|

Winter wheat (Triticum aestivum) response to Barley yellow dwarf virus at various nitrogen application rates in the presence and absence of its aphid vector, Rhopalosiphum padi

Abstract: Barley yellow dwarf (BYD) is one of the most common diseases of cereal crops, caused by the phloem‐limited, cereal aphid‐borne Barley yellow dwarf virus (BYDV) (Luteoviridae). Delayed planting and controlling aphid vector numbers with insecticides have been the primary approaches to manage BYD. There is limited research on nitrogen (N) application effects on plant growth, N status, and water use in the BYDV pathosystem in the absence of aphid control. Such information will be essential in developing a post‐inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Viral particles reduce meristematic activity in the vascular tissue of infected plants (Esau, 1957), which can disrupt differentiation and development of cellular organelles in infected phloem cells (Jensen, 1969), resulting in stunted growth and eventual necrosis of infected cells (Esau, 1957), culminating in the symptoms detailed in Table 1. Persistent infestation with virus‐carrying vectors can increase the severity of disease observed (Liang et al., 2019).…”
Section: Yellow Dwarf Virus and Yellow Dwarf Disease: A Brief Introdu...mentioning
confidence: 99%
“…Viral particles reduce meristematic activity in the vascular tissue of infected plants (Esau, 1957), which can disrupt differentiation and development of cellular organelles in infected phloem cells (Jensen, 1969), resulting in stunted growth and eventual necrosis of infected cells (Esau, 1957), culminating in the symptoms detailed in Table 1. Persistent infestation with virus‐carrying vectors can increase the severity of disease observed (Liang et al., 2019).…”
Section: Yellow Dwarf Virus and Yellow Dwarf Disease: A Brief Introdu...mentioning
confidence: 99%
“…Mantai et al (2015) observed in oats, growth in the biomass rate with the increase of doses of N-fertilizer in a single dose in the growing systems, a condition not always accompanied by the higher grain yield, results also verified in this research. In wheat, Liang et al (2019) found that the increase in nitrogen concentration in plant tissue significantly increased the biomass rate by applying the nutrient in a single dose. Research has indicated that the fractional supply of nitrogen can further decrease nutrient losses at the most propitious times for fertilization, improving the efficiency of the nutrient (Benin et al, 2012;Ferrari et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…While describing BYDV in 1953, Oswald and Houston [ 11 ] noted that damage caused by BYDV infection was particularly severe in a drought year, and others have also reported more severe yield losses from BYDV infection in years of lower rainfall [ 15 , 25 , 38 , 39 ]. Given that the root system of a plant infected with BYDV is also often just as stunted, and sometimes even more so, than the visible, above-ground portion of the plant [ 11 , 40 , 41 , 42 , 43 ], it has been suggested that the roots of infected plants may be too shallow to reach or obtain adequate water and nutrients in dry conditions [ 11 ]. This is one possible explanation for the especially severe yield losses observed in experiment 1, as 2015 was the second year in a row of well below average rainfall in the region ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%